Conditioned pain modulation using painful cutaneous electrical stimulation or simply habituation?. (11th April 2018) - Eitner, L.; Özgül, Ö.S.; Enax‐Krumova, E.K.; Vollert, J.; Maier, C.; Höffken, O.
Abstract: Background and Aims: Cold pressor test was recently reported to significantly reduce painful cutaneous electrical stimulation (PCES)‐induced pain and corresponding evoked potentials (PCES‐EPs), but whether this reduction is an effect of conditioned pain modulation (CPM) remains unknown. To what extent these findings are confounded by habituation is also unknown. We thus compared the effect of CPM and habituation on PCES‐induced pain and PCES‐EPs and analysed whether increased attention by a random change of electric stimulation would intensify this possible habituation effect. Methods: Three custom‐built concentric surface electrodes were used to induce a pain intensity of 60 on a 0–100 numerical rating scale (NRS) among 29 healthy subjects (age 20–35y, 16 females). PCES‐EPs (including P0N1 and N1P1 amplitudes, N1 latencies) were assessed over Cz. Group A received 14 min of electrical stimulation with constant intensity followed by 14 min of electrical stimulation with variable intensities, group B vice versa. Afterwards, subjects perceived cold‐water pain (10 °C) contralaterally as conditioning stimulus to assess CPM. Statistical analysis was conducted with ANOVA and t ‐test. Results: In both groups, N1 latencies remain unchanged, but the intensity of PCES‐induced pain (12 ± 17%; p  < 0.01) and N1P1 amplitudes of PCES‐EPs (10 ± 16%; p  < 0.05) decreased significantly during the 14‐min PCES with constant current intensity. CPM also significantly reduced pain ratings (36 ± 19%; p  < 0.001) and amplitudes (37.2 ± 15.8%), p  < 0.001). A significant decline of P0N1 amplitudes occurred only during CPM (18 ± 61%; p  < 0.001). Conclusion: We found a significant effect of habituation on PCES‐induced pain and PCES‐EPs, although the effect of CPM was significantly larger and could not be explained by habituation alone. Significance: Painful cutaneous electrical stimulation leads to moderate habituation of pain and evoked potential amplitudes, but the conditioned pain modulation effect using this method is significantly larger, which might indicate a different mechanism in central processing.